Analisis Faktor-Faktor yang Mempengaruhi Kepuasan Kerja Karyawan RS M di Kabupaten Pekalongan - Mokhammad Aji Edo Susanto; Chriswardani Suryawati; Septo Pawelas Arso (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2020)
RSI PKU Muhammadiyah Pekajangan Hospital always tries to develop existing services. The hospital must maintain services in order to satisfy all parties including its employees. The hospital sets the standard of employee satisfaction at 80%. The employee satisfaction survey continued to improve from 62.4% in 2015, 63.93% in 2016, to 72.29% in 2017 but has not yet reached the target. The research aims to analyze the factors that influence job satisfaction of RSI PKU Muhammadiyah Pekajangan Hospital employees.This type of research is quantitative with analytic methods and cross sectional study design. The number of samples is 172 people. The sample selection is done by optimum allocation stratified sampling. Data processing was performed by bifariate analysis using the Chi Square Test and multifariate analysis using multiple logistic regression tests.Employee satisfaction has reached 84.3%, exceeding the target set by the hospital. The work it self, awards / achievements, and coworkers have a significant relationship and influence on job satisfaction. Promotion, family support, payroll and benefits, work environment, and hospital policies have a relationship but the effect is less significant on job satisfaction. Leadership has no relationship with job satisfaction. The most influential factor on employee job satisfaction is the award / achievement factor with a Sig. = 0,000 and OR = 29,124.The award / achievement factor is the main factor so that the hospital needs to develop a management system that can adopt better awards / achievements with performance as a reference. Perceptions of payroll / benefits factors are also not good so it needs intervention. Giving awards in the form of additional payroll / benefits is expected to help increase job satisfaction.